PENERAPAN MODEL PEMBELAJARAN DIDI (DISCOVERY & DIGITAL LEARNING) UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP SISTEM PENCERNAAN PADA SISWA KELAS V SD - Nurul Fazriyah; Fitriana Nursyfa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
Identification of problems that arise in the material of the human digestive system in class V SDN Mekarjati IV is the low level of understanding of students' concepts in the material of the human digestive system. One of the learning models that can be used to overcome the above problems is to use the Didi learning model (Discovery & Digital learning). The goal to be achieved is to improve the ability to understand the concept of digestion in fifth grade students at SDN Mekarjati IV by applying the Didi learning model. The type of research conducted is classroom action research. This study aims to improve educational practices that appear in the learning process in the classroom. The design used in this research is a cyclical method. The subjects in this study were the fifth grade students of SDN Mekarjati IV with a total of 22 students. The results of increasing students' understanding of concepts after applying the Didi improvement learning model are categorized as good. In the first cycle, the results of the fifth grade students' concept understanding test were still far from what was expected with the percentage level of understanding of the concept of new students reaching 61.79%. And after the improvement in the second cycle, the percentage of students' conceptual understanding level increased to 81.32%. Thus, students' understanding of the concept of the digestive system material for class V at SDN Mekarjati IV after applying the Didi learning model (Discovery & Digital learning).